Tempi der Bewegung - Modi des Gefühls - Greifenstein, Sarah (Cinepoetics, 2020)
What is the connection between the tempo of audiovisual images and the audience`s emotional experience? Examining the screwball comedy of the 30s and 40s, this study looks at comedy and hilarity as temporal structures. Exchanges of blows, puns, and verbal acrobatics are embedded in a complex composition of voices, facial expressions, gestures, and visual constructions. The audience experiences and enjoys combat and rage as an elegant pas de deux.